A Protocol for a Rapid Realist Review of Literature Examining Co-Production in Youth Mental Health Services - Verity Rose Jones; Justin Waring; Nicola Wright; Sarah-Jane Hannah Fenton (Youth, 2023)
An overview of internationally published literature on what works for co-production in youth mental health services is missing, despite a practice and policy context strongly recommending this approach. The proposed rapid realist review aims to develop a theory about how and why co-production methods in youth mental health services work (or do not work), for whom, in which contexts, and through what mechanisms. Relevant evidence will be synthesised to develop context–mechanism–outcome (CMO) configurations that can inform policy and practice. Stakeholders will be iteratively involved in the development of these theories (CMO configurations) by engaging an expert panel and youth advisory group. The review results will be reported according to the RAMESES guidelines and are intended to be published in an academic journal. Additionally, a plain English summary will be produced with the support of the youth advisory group.